Food security and morbidity of elderly in disadvantaged rural Bangladesh - Quddus, MA; Bauer, S (Journal of the Bangladesh Agricultural University, 2014)
The study was undertaken to assess the food consumption level, prevalence of food insecurity and health status of elderly in the disadvantaged rural area of Bangladesh. Data were collected from fifteen villages in three vulnerable regions (river-flooded, hilly and coastal) through self-completed questionnaire. Descriptive statistics of sociodemographic characteristics of 282 households, food frequency and overall health status of elderly were measured. Economic, demographic and some other household characteristic factors influencing food insecurity of elderly people was estimated using binary logistic regression model. Socio-demographic factors influencing morbidity of elderly people were estimated using Chi-square statistics. Socioeconomic conditions of the studied areas were poor and they spent above 83% of their income for food. Rice, wheat, pulses and vegetables were the highly consumed and fruits and sweets were the less consumed foods by the elderly people. One-fourth and two-third of the elderly people had eaten fish and meat, respectively less than a week. Food insecurity was inversely associated with household income and level of education of elderly people and positively associated with number of household member. Food security was 3.5 times more likely to the oldest elder (75 years) as compared with older elder (< 75 years). Elderly people of age group 75 years and over were more prevalence of morbidities and 23.8% elders were suffering from severe morbidity. Also they suffered from treatment facilities. Higher age, low income, food insecurity and anxiety were the major causes of their morbidity. No significant morbidity differentials existed among different sexes, farm size and study locations. Proper intervention programs should be designed and implemented to control the prevalence of health and food availability for the elderly. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21254 J. Bangladesh Agril. Univ. 12(1): 95-104, June 2014